Diversity and Composition of Endophytic Fungal Communities Associated with Cocoa (Theobroma cacao L.) Fruits in the Northern Ecuadorian Amazon - Pablo Israel Alvarez-Romero; Daniel Arturo Román-Robalino; Eduardo Patricio Salazar-Castañeda; Sandra Elizabeth Suárez-Cedillo; Leonardo Anibal Hinojosa-Sánchez; Ana Francisca Tibúrcia Amorim Ferreira e Ferreira; Miguel Angel Guallpa-Calva (International Journal of Plant Biology)
The study of microorganisms associated with tropical plant species, particularly fungi, has garnered significant interest due to their potential applications in biological control and the synthesis of pharmacologically active compounds. This research aimed to identify and characterize the endophytic fungal communities associated with cocoa (Theobroma cacao L.) fruits across three municipalities in the Orellana province, located within the Ecuadorian Amazon. Fungi were isolated directly from cocoa fruits and analyzed through comprehensive cultural, morphological, and molecular analyses. The diversity of fungal taxa was evaluated using metrics of relative abundance and species richness. A total of 464 fungal isolates were obtained, representing 56 distinct morphotypes and 14 genera within the phylum Ascomycota. The most abundant genera included Penicillium sp. (27.8%), Epicoccum sp. (20.5%), Lasiodiplodia sp. (10.1%), Trichoderma sp. (9.91%), and Fusarium sp. (9.70%). Notably, in the municipality of La Joya de los Sachas, a higher number of endophytic fungi was observed, encompassing 14 genera. This study provides critical insights into the diversity and distribution of fungal communities associated with cocoa fruits in the northern Ecuadorian Amazon. These findings have important implications for the management of cocoa diseases and the discovery of novel bioactive compounds. Future investigations should explore the functional roles of these fungi, particularly their potential as biocontrol agents or sources of novel pharmaceuticals. Furthermore, examining the effects of environmental variables and agricultural practices on cocoa fruit mycobiota may contribute to a deeper understanding of the ecological dynamics within this system.